Flavour Profile of Ghee by Gas Chromatography Mass Spectrometry (Gc-Ms): A Mini Review - , Rashmi Rekha Saikia; , Rajendra Nath Borpuzari; , Trishna Borpuzari; , Masuk Raquib; , Kushal Jyoti Thakuria (Archives of Current Research International, 2025)
Ghee, a clarified milk fat, is known for its rich and complex flavour, which arises from a diverse array of volatile compounds formed during heat clarification. This article explores the flavour profile of ghee using Gas Chromatography-Mass Spectrometry (GC-MS) and identifies key volatile components including carbonyls, lactones, free fatty acids (FFAs), esters, and miscellaneous compounds. The formation of these volatiles is influenced by factors such as the method of preparation, temperature and duration of clarification, acidity of raw materials, and microbial activity during fermentation. Traditional ghee, especially that prepared from ripened cream or butter, shows a higher concentration and diversity of flavour compounds compared to industrial counterparts. Compounds such as methyl ketones, δ-lactones, and specific FFAs are found to be primary contributors to the characteristic aroma and taste of ghee. The study also examines how feed, season, and enrichment with aromatic herbs affect ghee's volatile profile. These findings underscore the intricate biochemical transformations responsible for ghee flavour and highlight the potential of GC-MS as a powerful tool for its characterization.